Hubungan kadar vitamin D plasma dengan IMT dan umur pada kanker payudara - Zakirullah Syafei; Sri W Suryani; Denny S Rifsal (AcTion: Aceh Nutrition Journal, 2018)
Breast cancer is the most common type of cancer in women worldwide. Statistics show breast cancer is the second leading cause of death after lung cancer. Vitamin D is believed to have anti-carcinogenic properties independently effective in protecting against breast cancer, biologically active vitamin D, can inhibit cell proliferation, induction of differentiation and apoptosis and inhibit angiogenesis in normal and malignant breast cells. Basal metabolic index (BMI) affects the bioavailability of vitamin D. Also the incidence of cancer increases with age, especially the age group> 40 years. The objective to analyze the relationship of plasma vitamin D levels with BMI and age in breast cancer. Method shaped analytic observational study with a cross-sectional design. A total of 53 outpatient breast cancer patients at Medan General Hospital were selected as study subjects using consecutive sampling technique. Serum 25 (OH) D testing used an enzyme-linked immunoabsorbent assay method. BMI data is obtained by measuring the body weight and height and age of the respondents' interviews. Data analysis used Spearman correlation statistical test. Results,  the mean vitamin D levels of the study subjects were 28,2 ± 8,9 ng / mL, BMI 25,5 ± 4,6 kg / m2, and subject age 51.1 ± 10,2 years. These results indicate normal vitamin D levels, a slightly high BMI and> 40 years of age. Statistical test results showed that there was a relatively weak relationship between plasma vitamin D levels and BMI (r = 0,2; p = 0,42) and age (r = 0,15; p = 0,86) breast cancer patients. Conclusion, there was no significant relationship between plasma vitamin D levels and the metabolic basal index and age in breast cancer patients.Kanker payudara merupakan jenis kanker yang paling umum terdapat pada wanita di seluruh dunia. Vitamin D memiliki sifat anti karsinogenik secara independen efektif dalam melindungi dari kanker payudara, secara biologis vitamin D aktif, dapat menghambat proliferasi sel, induksi deferensiasi dan apoptosis serta menghalangi angiogenesis pada sel payudara normal dan maligna. Indeks Masa Tubuh (IMT) berpengaruh terhadap bioavaibilitas vitamin D. Tujuan untuk menganalisis  hubungan kadar vitamin D plasma dengan IMT dan umur pada kanker payudara. Penelitian menggunakan studi observasional analitik dengan desain cross sectional. Sebanyak 53 pasien kanker payudara rawat jalan di RSUP-HAM Medan dipilih sebagai subjek penelitian menggunakan tehnik consecutive sampling. Pengujian serum 25(OH)D menggunakan metode enzyme-linked immunoabsorbent assay. Data IMT diperoleh dengan pengukuran berat badan dan tinggi badan serta umur dari hasil wawancara responden. Analisis data menggunakan uji statistik korelasi spearman.  Hasil, rerata kadar vitamin D subjek penelitian adalah 28,2±8,9 ng/mL, IMT 25,5±4,6 kg/m2, dan usia subjek 51,1±10,2 tahun. Hasil ini menunjukkan kadar vitamin D normal, IMT sedikit tinggi dan usia > 40 tahun. Hasil uji statistik, menunjukkan bahwa terdapat hubungan yang tergolong lemah antara kadar vitamin D plasma dengan IMT (r=0,2; p=0,42) dan usia (r=0,15; p=0,86) pasien kanker payudara. Kesimpulan, tidak terdapat hubungan yang signifikan antara kadar vitamin D plasma dengan indek masa tubuh dan usia  pada pasien kanker payudara.